2013
DOI: 10.1097/mib.0b013e3182813482
|View full text |Cite
|
Sign up to set email alerts
|

Practical Strategies for Enhancing Adherence to Treatment Regimen in Inflammatory Bowel Disease

Abstract: Promoting adherence to treatment among pediatric and adult patients with inflammatory bowel disease (IBD) is a critical yet challenging task for health care providers. Several existing interventions to enhance adherence among individuals with IBD offer useful information about practical strategies to enhance adherence. The current review article has 3 goals. First, the review provides a context for understanding treatment regimen adherence in IBD by reviewing key definitional, measurement, and conceptual chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 57 publications
1
78
0
Order By: Relevance
“…So additional care by clinical pharmacist resulted in improved medication adherence. Study conducted by Greenley R et al 26 proved that specific IBD education about its effects and management can possibly enhance patient adherence and improve the patients 'outcome. Majority of our patients had involuntary non-adherence.…”
Section: Discussionmentioning
confidence: 99%
“…So additional care by clinical pharmacist resulted in improved medication adherence. Study conducted by Greenley R et al 26 proved that specific IBD education about its effects and management can possibly enhance patient adherence and improve the patients 'outcome. Majority of our patients had involuntary non-adherence.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published review of IBD that included 10 studies with a total of 1267 patients found that strategies such as education, regimen simplification, reminder systems and organisational strategies seem to increase medical adherence. [11] A simple and inexpensive method of measuring adherence is self-reporting. Moreover, it is most likely that patients reporting non-adherence are being truthful and that the results are valid.…”
Section: Introductionmentioning
confidence: 99%
“…In brief, measuring adherence is very challenging in chronic diseases; there is no gold standard test to assess adherence to oral medication and therefore multi-method approaches are needed to get a true adherence estimate over a period of time [3,10,11].…”
Section: Medication Adherence In Childrenmentioning
confidence: 99%